2018
DOI: 10.1016/j.dsr2.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of deep water mass investigation in the Weddell Sea (1984–2014): Temporal variability and changes

Abstract: Running title: Weddell deep waters variability Highlights  Shifts in Weddell Sea Bottom Water (WSBW) properties towards less dense varieties likely equate to less WSBW being produced over time.  The decline of WSBW volume ceased around 2005 and likely recovering after that.  Dense Shelf Waters drive and modulate the recent WSBW variability.  WSBW is composed by 71% of Warm Deep Water and 29% of Dense Shelf Waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 107 publications
(134 reference statements)
2
29
0
Order By: Relevance
“…In this matter, the low spinup period of 1 year in SoSE and the lack of spinup in ECCO2 could have allowed instability in water column in the reanalysis, hence weakening stratification. However, the WDW increase reported here is consistent with the observed results reported by Kerr et al (2017), who found a slight increase in the WDW contribution to the total mixture of deep and bottom waters in the Weddell Sea from 1984 to 2014, despite the high degree of interannual variability. However, since no real open ocean polynya has been reported for this period, a critical analysis of the model mechanisms of heat exchange between the surface waters and sea ice is required in the future to efficiently understand the role of WDW in open ocean polynya establishment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this matter, the low spinup period of 1 year in SoSE and the lack of spinup in ECCO2 could have allowed instability in water column in the reanalysis, hence weakening stratification. However, the WDW increase reported here is consistent with the observed results reported by Kerr et al (2017), who found a slight increase in the WDW contribution to the total mixture of deep and bottom waters in the Weddell Sea from 1984 to 2014, despite the high degree of interannual variability. However, since no real open ocean polynya has been reported for this period, a critical analysis of the model mechanisms of heat exchange between the surface waters and sea ice is required in the future to efficiently understand the role of WDW in open ocean polynya establishment.…”
Section: Discussionsupporting
confidence: 82%
“…The highest AABW formation observed in the UR025.4 product occurred mainly east of the Weddell Sea sector. Those findings agree with the theory proposed by Meredith et al (2000) that AABW present in the Weddell Sea receives considerable input of AABW varieties from the east, such as the recently observed evidence in the Southern Ocean (e.g., Jullion et al, 2014;Kerr et al, 2017). The entrainment of UCDW in the Indian Ocean sector created an equilibrium between melting and freezing that favored LCDW salinization and led to coastal deep convection.…”
Section: Discussionsupporting
confidence: 81%
“…This forcing has effects outside the Weddell Sea, with Meijers et al () arguing that the intermittent presence of a cold, fresh slope current north of Elephant Island is attributable to variable export from the Weddell Sea, driven in turn by wind‐driven acceleration of the boundary current. Kerr et al () have also argued for a long‐term decline in the densest constituent of this bottom water, the WSBW, though some recovery in volume has occurred since 2005.…”
Section: Physical Oceanographymentioning
confidence: 99%
“…Ventilation of the abyssal waters of all oceans is thus affected, but also CO 2 (natural and anthropogenic), nutrients, and DOC and suspended particles, including microorganisms, are transported northward from the WG. Since limited sampling is available during water‐mass formation, it is unknown what the physical, chemical, and biological properties of the contributing water masses are at their start, even when some knowledge about water mass fractions within the WG may be gained from data analysis (Kerr et al, ). The state of the water mass upon formation is the preformed state, which is needed in calculations of water properties further downstream, for example, the back‐calculation of anthropogenic CO 2 , or the transit time distribution.…”
Section: Synthesis and Outlookmentioning
confidence: 99%
“…The Weddell Sea is the backdrop for ocean and cryosphere processes that have important implications for local environmental conditions and global climate. Over half of the densest and deepest water in the world's oceans, Antarctic Bottom Water (AABW), is sourced from parent waters formed on the Weddell Sea southern and western continental shelves (Gordon et al, 1993; Kerr et al, 2018; Orsi et al, 1999; van Caspel et al, 2015). The properties and production rate of this water mass have implications for global ocean circulation and climate regulation as AABW supplies the lower limb of the global overturning circulation.…”
Section: Introductionmentioning
confidence: 99%